Lump Kinetic Analysis of Syngas Composition Effect on Fischer-Tropsch Synthesis over Cobalt and Cobalt-Rhenium Alumina Supported Catalyst - Dewi Tristantini; Ricky Kristanda Suwignjo (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2016)
This study investigated lump kinetic analysis of Fischer-Tropsch synthesis over Cobalt and Cobalt-Rhenium Alumina supported catalyst (Co/γ-Al2O3 and Co-Re/γ-Al2O3) at 20 bars and 483 K using feed gas with molar H2/CO ratios of 1.0 to 2.1. Syngas with H2/CO molar ratio of 1.0 represents syngas characteristic derived from biomass, while the 2.1 molar ratio syngas derived from coal. Rhenium was used as the promoter for the cobalt catalyst. Isothermal Langmuir adsorption mechanism was used to build kinetic model. Existing kinetic model of Fischer-Tropsch synthesis over cobalt alumina supported catalysts only valid for operating pressure less than 10 bar. CO insertion mechanism with hydrogenation step of catalyst-adsorbed CO by catalyst-adsorbed H component as the rate-limiting step is valid for operating condition in this research. Higher H2/CO ratio makes faster hydrogenation step and less-product dominated in the associative CO adsorption step and dissociative H2 adsorption equilibrium step. Kinetic constant for hydrogenation step increases 73-421% in syngas with 2.1 H2/CO molar ratio compared to condition with 1.0 H2/CO molar ratio. Faster hydrogenation step (with higher kinetic constant) results in higher reactant conversion. Equilibrium constant for associative CO adsorption and dissociative H2 adsorption step decreases 53-94% and 13-82%, respectively, in syngas with higher H2/CO molar ratio. Less product dominated reactant adsorption step (lower equilibrium constant for CO and H2 adsorption step) gives higher CH4 product selectivity, which occurred on 2.1 molar ratio of syngas. Rhenium (Re) metal on cobalt catalyst with composition 0.05%Re-12%Co/γ-Al2O3 only gives effect as structural promoter, which only increases reactant conversion with the same product selectivity.